Current Limitations of Intraoperative Ultrasound in Brain Tumor Surgery - Šteňo, Andrej; Buvala, Ján; Babková, Veronika; Kiss, Adrián; Toma, David; Lysak, Alexander (Frontiers in Oncology, 2021)
While benefits of intraoperative ultrasound (IOUS) have been frequently described, data on IOUS limitations are relatively sparse. Suboptimal ultrasound imaging of some pathologies, various types of ultrasound artifacts, challenging patient positioning during some IOUS-guided surgeries, and absence of an optimal IOUS probe depicting the entire sellar region during transsphenoidal pituitary surgery are some of the most important pitfalls. This review aims to summarize prominent limitations of current IOUS systems, and to present possibilities to reduce them by using ultrasound technology suitable for a specific procedure and by proper scanning techniques. In addition, future trends of IOUS imaging optimization are described in this article.